Postural Control in Preschool Children with Developmental Coordination Disorder, in Sitting Position During a Functional Task - Mercê, Cristiana (2018)
The developmental coordination disorder is a motor disorder that affects 5 to 6% of children at school-age. The postural control deficit is one of the most prevalent problems affecting 73 to 87% of these children. The present research aims to analyze and compare postural control in probable (p-DCD) and at- risk of developmental coordination disorder children and in typical children in a sitting position during a functional task. p-DCD children were tendentially less recurrent, less periodic, simpler and more regular. These children oscillated more and faster in conditions with visual information; with a visual focus they had more stability and oscillated less and slowler campared to the baseline; without visual information they reduced their oscillations and velocity and become less recurrent, periodic, stable and simpler, possibly freenzing more degrees of freedom in order to respond to absence of external information. p-DCD seem to be more dependent on external stimulus like visual information to auto organize their own balance. The greater the task’s complexity, the lesser and slower their oscillations were but also more recurrent and periodic. Despite oscillating, more and faster in all conditions and being tendentially more recurrent and periodic, in risk children revealed a behaviour pattern similar to typical in both variables. p-DCD, at-risk and typical children reveal the same manner of action without visual information, less and slower oscillations. Most likely, the problem with p-DCD is not in motor control, but on perception-action cycles’ effectivness; and, where stimulation must be focused.